Influence of temperature on accuracy of height connection measurement. Issue 1 (2nd January 2016) - Mučková, Jitka; Dandoš, Rostislav; Jadviščok, Petr; Konečný, Miroslav
Abstract: The purpose of depth measurement is to bring the altitude from the surface to the connected horizon (level) by means of a vertical mine. Points, for which the height is determined in this way, are part of the fundamental mining vertical control, and their height should therefore be determined as accurately as possible. There are several ways of this measurement and the temperature has influence on accuracy of each of them. The paper is dedicated to evaluation of influence of temperature, applying results of height connection measurement carried out at Karviná mine. Two measurements were performed in ČSA 2 shaft and the other in shaft Mír 5 of Darkov mine in Ostrava-Karviná Coal District, CZE. Height connection measurement by a vertical mining work was done in two ways: using the depth tape and using the electro-optical distance meter.